If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying df = g + -10 Reorder the terms: df = -10 + g Solving df = -10 + g Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Divide each side by 'f'. d = -10f-1 + f-1g Simplifying d = -10f-1 + f-1g
| 6(-2t+8)=-84 | | 7(-5+n)=-28 | | 4(2+a)=44 | | 6(2a+10)=96 | | 5(5+6n)=-215 | | 15a-54=-3 | | 7(-5+3k)=175 | | an=3+(n-1)(-5) | | (2x+10)=(86+x) | | 81=.5(9)h | | 76+x=180 | | X+7X-6=20 | | F(x)=-2x+2 | | 7(5w+8)=21 | | 2(3d+1)=-52 | | 4(-1+3d)=92 | | 5(4x+10)=190 | | 4(5+5t)=60 | | 2(3b-8)=14 | | 5k^2-34k-7=0 | | 8n+2=17 | | 2(4+5w)=98 | | 20-x/3=x/10 | | 5k^2-34k-7=o | | 2(1-2k)=-10 | | 7(4x+2)=350 | | 3(10+4b)=66 | | 3w+=2 | | 7(1k-10)=-7 | | 0.1=15x+0.56x^2 | | 3(5t-8)=141 | | 18=.5h(6+1.2) |